2005
DOI: 10.1111/j.1537-2995.2005.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon cold: could 4°C storage improve platelet function?

Abstract: ABBREVIATIONS: b-GlcNAc = b-N-acetylglucosamine; HSR = hypotonic shock response. n 1969, Murphy and Gardner 1 demonstrated that transfused human platelets (PLTs) that have been stored at 4∞C are rapidly cleared from the circulation. They and others proved that PLTs stored at room temperature (22∞C) show significantly better recovery and survival, with a typical life span of 7 to 9 days versus only 2 to 4 days for refrigerated PLTs. 1-4 This odd phenomenon of chilled PLT clearance has had profound consequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 68 publications
0
21
0
1
Order By: Relevance
“…In addition, RBCs-WBCs interactions are known to be important in postcapillary venules (32) and WBCs from SCA patients seem to be more adhesive to SRBCs (45) and are capable of forming aggregates of few cells in whole blood (46). Moreover, the drastic morphology change we observe for the aggregate could be correlated to the known activation of platelets observed during blood storage at 4 C (47,48). It has been reported in particular that activated platelets are able to form aggregates in a shear microgradient (49), in locations analogous to the corner of the pillars of this device, but for much higher Reynolds number flow conditions, not relevant for the microcirculation.…”
Section: Effect Of Autologous Plasma In Combination With Platelets Anmentioning
confidence: 55%
“…In addition, RBCs-WBCs interactions are known to be important in postcapillary venules (32) and WBCs from SCA patients seem to be more adhesive to SRBCs (45) and are capable of forming aggregates of few cells in whole blood (46). Moreover, the drastic morphology change we observe for the aggregate could be correlated to the known activation of platelets observed during blood storage at 4 C (47,48). It has been reported in particular that activated platelets are able to form aggregates in a shear microgradient (49), in locations analogous to the corner of the pillars of this device, but for much higher Reynolds number flow conditions, not relevant for the microcirculation.…”
Section: Effect Of Autologous Plasma In Combination With Platelets Anmentioning
confidence: 55%
“…Also, refrigerated platelets could theoretically have functional advantages over room temperature platelets, although this is unproven in vivo. 37 When murine platelets are cooled to 4°C for 2 hours, von Willebrand factor receptor (GPIb) complexes cluster together irreversibly on the platelet surface. In this clustered conformation, platelet GPIb molecules are specifically bound by α M β 2 integrin receptors on liver macrophages.…”
Section: Refrigerated Storage Of Platelets?mentioning
confidence: 99%
“…In recent years, Hoffmeister and colleagues have shown that platelet clearance and function may be entirely separate attributes, and that appropriate modification (such as glycosylation) may prolong platelet survival in circulation (15-17). Concurrent reports from several groups have confirmed that platelets stored at 4°C are “healthier” than platelets stored at room temperature (18). Together, these studies have prompted the reconsideration of cold stored platelets as a transfusion product to treat bleeding patients (18-20).…”
Section: Introductionmentioning
confidence: 98%